Sumber Rezeki Dalam Perspektif Al-Quran dan Hadits - Kaspia, Yola; Tarigan, Azhari Akmal; Syahriza, Rahmi (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
This research aims to reveal the meaning of the word Fortune and the doors to obtaining sustenance based on the signs of the Koran. This research includes qualitative descriptive research with a thematic interpretive research format. This research data is secondary. Secondary data is data that contains ideas, ideas and interpretations of interpreters. The results of this research show that the word